2019
DOI: 10.3390/ijerph16142538
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Smoking Cessation Quitline in Vietnam: Evidence Base and Future Directions

Abstract: Smoking is considered the most critical modifiable factor with regard to lung cancer and remains a public health concern in many countries, including Vietnam, which is among those countries with the highest tobacco consumption rates in the world. This study has examined the impact of national telephone counselling for smoking cessation and has identified the factors associated with the impact of the quitline among male callers in Vietnam. A randomized cross-sectional survey of 469 smokers who sought smoking ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Hence, HCWs will be highly receptive to comprehensive smoking cessation support, such as free nicotine replacement, staff counselling, and smoking quit lines. 21,22 Second, this study demonstrates the strong receptiveness of staff to smoking bans within health care facilities-even among smokers. Just 20% of workers felt that a ban would be unfair to smokers, and 78% felt a smoking ban would improve their job performance.…”
Section: Discussionmentioning
confidence: 70%
“…Hence, HCWs will be highly receptive to comprehensive smoking cessation support, such as free nicotine replacement, staff counselling, and smoking quit lines. 21,22 Second, this study demonstrates the strong receptiveness of staff to smoking bans within health care facilities-even among smokers. Just 20% of workers felt that a ban would be unfair to smokers, and 78% felt a smoking ban would improve their job performance.…”
Section: Discussionmentioning
confidence: 70%
“…We agree with the recommendation from the GATS 2015 that the national cessation programme should be strengthened in order to better reach those smokers who do not access healthcare. A recent study showed a positive result about the toll-free quit line run by Bach Mai Hospital [ 23 ]. Currently, this quit line provides around 10 follow-up counselling calls over 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed a positive result about the toll-free quit line run by Bach Mai Hospital [23]. Currently, this quit line provides around 10 follow-up counselling calls over 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal well-being was measured using the WHO-5 (5 items) to understand subjective well-being during the past two weeks (Hatcher et al, 2016;Ngo et al, 2019;Topp et al, 2015) based on a 6-point Likert response (ranging between "all of the time -0", to "at no time-5"). Raw scores were standardised in 100 points and a higher score indicated greater well-being.…”
Section: Outcome Variablesmentioning
confidence: 99%